Epidemiological and clinical characteristics of COVID-19 mortality among healthcare workers in Saudi Arabia: A nationwide study - Bashaier A. Aljohar; Mohammed A. Kilani; Anfal A.Al Bujayr; Tabish Humayun; Manar J. Alsaffar; Khalid H. Alanazi (Elsevier, 2022)
Background: Healthcare workers (HCWs) have been highly affected by COVID-19 due to their fundamental duties in diagnosing, caring, and treating the rapidly increasing number of infected patients. Thus, are facing the occupational risk of COVID-19 infection and mortality. Purpose: To investigate the COVID-19 disease clinical characteristic and associated factors among HCWs in Saudi Arabia. Methods: This was a nationwide, retrospective analytical study conducted from 5th of March 2020-21 st of August 2021. All deceased HCWs who were diagnosed with COVID-19 were included in this study. Results: As of August 21, 2021, a total of 305 deaths were recorded due to COVID-19 infection among HCWs in all Saudi healthcare facilities. The case fatality rate was 0.35%. Deaths were highest among physicians (40.0%). Most of deceased HCWs acquired the infection from the community (80%). 71% of deceased HCWs had at least one chronic medical condition. Most of them were admitted to ICU before they passed away (83.6%). Three significant variables predicting ICU admission were presence of one or more comorbidities, hypertension, and chronic respiratory diseases Conclusion: HCWs are at higher risk for exposure to COVID‐19 due to their occupational risk. Our study encourages future research to provide more comprehensive information regarding COVID-19 morbidity and mortality among HCWs.